Wheat–Lentil Mixed Cropping System Productivity Under Varied Irrigation Levels (Annals of Bangladesh Agriculture, 2022)
The study on mixed cropping of lentil and wheat was conducted under three levels of irrigation. Wheat at 10, 15, 20, 25, 30, 35, 40, 45 and 50% of the normal seed rates were mixed with full seed rate of lentil to find out a suitable mixing rate of wheat for maximum total yield from unit land. The study was conducted in a split plot design with three replications. Lentil yields obtained with single and two irrigations were identical and higher than with no irrigation. The highest wheat yield was obtained with two irrigations. Total yield was the highest with application of two irrigations. Mixing different proportions of wheat with lentil produced 95-171% additional yield over sole cropping of lentil. Mixing of wheat at 25-35% with lentil was found to be judicious for obtaining maximum total yields. The highest protein yield was obtained with 30-35% and 35% mixing rates of wheat at zero and single irrigation levels. Growing wheat with lentil resulted in increased protein yield in wheat than sole cropping. The highest land equivalent ratio (LER) values were obtained when 30-35% of wheat seed rate were mixed with lentil. Application of two irrigations resulted in high LER values. It is concluded that use of 35% of wheat seed rate along with full seed rate of lentil under two levels of irrigations would be the best mixing ratio for obtaining the highest wheat and total grain yield.Ann. Bangladesh Agric. (2021) 25 (1) : 1-10